Innovation in Childhood Education with the Assistance of the Application “Filmora GO” - Lenz, Diones Patricia; Felin, Maira Cristina; Bavaresco, Paulo Ricardo (Cadernos de Educação Tecnologia e Sociedade, 2022)
The reflections in this article aim to discuss and address principles on innovation in education and share innovations in the practice of early childhood education using the Filmora Go (Vlogit) application. Given the current circumstances and the lack of theoretical and practical basis in schools in relation to technological content, it was decided to present a new tool to subsidize new knowledge, thus improving the work methodology of each teacher. The collective construction of actions aimed at the technological and innovative world breaks with repetitive and monotonous practices, thus building other possibilities of education in the daily life of schools. Having the understanding that innovation in early childhood education comes to contribute to the teaching method, we can emphasize (reflect) that we must increasingly enhance the search for quality education. In search of these exchanges of knowledge, authors were used as a reference to build a theoretical debate, some of which are: Carbonell (2002), Belloni (2005) and Hoffmann (1991). Questions were approached with the teachers to understand what it is to innovate in the actions taken by them and the importance of these actions in the school routine.